Is Hospital Competition Socially Wasteful? - Kessler, D. P.; McClellan, M. B. (Quarterly Journal of Economics, 2000)
We study the consequences of hospital competition for Medicare beneficiaries' heart attack care from 1985 to 1994. We examine how relatively exogenous determinants of hospital choice such as travel distances influence the competitiveness of hospital markets, and how hospital competition interacts with the influence of managed-care organizations to affect the key determinants of social welfare—expenditures on treatment and patient health outcomes. In the 1980s the welfare effects of competition were ambiguous; but in the 1990s competition unambiguously improves social welfare. Increasing HMO enrollment over the sample period partially explains the dramatic change in the impact of hospital competition.